2016
DOI: 10.1109/jmems.2016.2562609
|View full text |Cite
|
Sign up to set email alerts
|

VO2-Based MEMS Mirrors

Abstract: This paper reports the integration of vanadium dioxide (VO 2 ) thin films in a microelectromechanical systems (MEMS) mirror device, where the actuation is mainly due to the solid-solid phase transition of VO 2 . The fabrication process described in this paper provides the details that will enable the integration of VO 2 thin films at any step during the fabrication of rather complex MEMS devices. The present VO 2 -based MEMS mirror device is operated electro-thermally through integrated resistive heaters, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…The added stress can move the transition temperature of the VO2, which has been observed previously in VO 2 thin films [42,43]. Even more relevant to the present case, this effect was also observed in VO 2 -based MEMS mirrors [10], where it was found that individual leg actuation and piston-like actuation required different actuation voltages—note that, during individual actuation, the remaining mirror legs add a stress that is not present during piston-like movement. The pseudo-creep is not included in the modeling of the device, in order to focus on the fundamental thermal and mechanical dynamics in the general case, and, as verified in later experiments, the presented model (ignoring the creep effect) shows adequate capability in predicting the mirror dynamics.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The added stress can move the transition temperature of the VO2, which has been observed previously in VO 2 thin films [42,43]. Even more relevant to the present case, this effect was also observed in VO 2 -based MEMS mirrors [10], where it was found that individual leg actuation and piston-like actuation required different actuation voltages—note that, during individual actuation, the remaining mirror legs add a stress that is not present during piston-like movement. The pseudo-creep is not included in the modeling of the device, in order to focus on the fundamental thermal and mechanical dynamics in the general case, and, as verified in later experiments, the presented model (ignoring the creep effect) shows adequate capability in predicting the mirror dynamics.…”
Section: Resultssupporting
confidence: 81%
“…The VO 2 -based MEMS mirror presented here follows the same fabrication process as in [10], but different metal layers are used to increased the yield per wafer—this is discussed in more detail in Section 2.2. Device fabrication starts with a two–inch double–sided p-type <111> polished Si wafer as the substrate with a thickness of 300 sans-serifμnormalm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations